Phylogeography of Dasia Gray, 1830 (Reptilia: Scincidae), with the description of a new species from southern India - Harikrishnan, S.; Vasudevan, Karthikeyan; de Silva, Anslem; Deepak, V.; Kar, Niladri Bhusan; Naniwadekar, Rohit; Lalremruata, Albert; Prasoona, K. Rebekah; Aggarwal, Ramesh K (Zootaxa, 2012)
A new tree skink species of the genus Dasia Gray, 1830, closely allied to Dasia haliana, is described from southern West-ern Ghats of India. The new species named, Dasia johnsinghi sp. nov. can be distinguished from all other congeners bymorphological and molecular data. A related species, Dasia subcaeruleum, is re-described based on new material from anew locality in the Western Ghats. Mitochondrial rDNA-based phylogenetic analysis of the genus Dasia reveals the affin-ities of the south Indian and the Sri Lankan species with Southeast Asian ones. The biogeographic processes that mighthave led to the disjunct distribution of the entities in the genus are discussed. An updated key to the identification of species of the genus Dasia is provided.